2016
DOI: 10.1002/pen.24314
|View full text |Cite
|
Sign up to set email alerts
|

Rotomolded polyethylene-agave fiber composites: Effect of fiber surface treatment on the mechanical properties

Abstract: In this work, a comparison between different agave fiber surface treatments has been presented to improve the mechanical properties of rotomolded natural fiber composites (NFC). The fiber treatments were carried out with sodium hydroxide, 2-chlorobenzaldehyde, maleic anhydride grafted polyethylene, acrylic acid, methyl methacrylate, and triethoxy vinyl silane. In particular, a simple dry-blending technique was used to introduce agave fibers in the polymer matrix (linear medium density polyethylene). The sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 45 publications
4
44
0
Order By: Relevance
“…For compression molding, the elongation at break decreased from 3.5% (PLA) to around 2.1% (biocomposites). For both processing methods, the elongation at break reduction is related to the low elasticity of agave fibers . The statistically significant lower elongation at break of CM‐BC samples compared to rotomolded ones is probably related to the higher stiffness and strength of the compression‐molded composites as lower porosity allows for better interfacial stress transfer leading to stiffer and more brittle materials.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…For compression molding, the elongation at break decreased from 3.5% (PLA) to around 2.1% (biocomposites). For both processing methods, the elongation at break reduction is related to the low elasticity of agave fibers . The statistically significant lower elongation at break of CM‐BC samples compared to rotomolded ones is probably related to the higher stiffness and strength of the compression‐molded composites as lower porosity allows for better interfacial stress transfer leading to stiffer and more brittle materials.…”
Section: Resultssupporting
confidence: 90%
“…This increase is mostly related to the higher agave fibers skeletal density (also called true or cell wall density) of 1.43 g/cm 3 . Cisneros‐López et al reported similar results for agave fiber reinforced PE composites produced by compression molding and rotomolding . On the other hand, it was observed that the bulk density of rotomolded (R‐BCs) and compression‐molded (CM‐BCs) biocomposites depends on the processing method.…”
Section: Resultssupporting
confidence: 84%
“…As mentioned above, this is related to poor interfacial adhesion between the fibers and the matrix [16]. To improve the interfacial interaction/adhesion, coupling agents and fiber surface treatments can be used [38]. When comparing the impact resistance results (Figure 8 and The results of Gardner's impact strength test on the outer surface and the inner surface as a function of ACA and AF content are shown in Figure 9.…”
Section: Morphologymentioning
confidence: 99%
“…Natural fiber flour reinforced composites are of great interest because of their recyclable, environmental friendly, biodegradable, and low cost characteristics . In addition, these composite materials may be used for engineering, packaging, automotive, and construction applications owing to their high strength to weight ratio, nontoxicity, and ease of processing . However, it has to be noted the presence of the natural fibers in a polymer matrix creates porosity at the interfaces owing to the interfacial tension between the hydrophilic fibers and the relatively hydrophobic polymer .…”
Section: Introductionmentioning
confidence: 99%